2021
DOI: 10.18632/aging.203610
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased gray matter volume and increased white matter volume in patients with neovascular age-related macular degeneration: a voxel-based morphometry study

Abstract: Objective: To measure white and gray matter volume (WMV, GMV) in patients with neovascular age-related macular degeneration (nAMD) using voxel-based morphometry (VBM). Material: Eighteen patients (9 men, 9 women) with nAMD and 18 (9 men, 9 women) healthy controls (HCs) aligned were recruited. Functional magnetic resonance imaging (fMRI) and VBM of three-dimensional T1 brain images were analyzed. And we also apply t-tests to look for GMV and WMV differences between groups. Correlation analysis was ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…25, 26 In addition, previous studies have found that both the volume of BG are found to decrease with age in healthy volunteers. 27, 28 In this study, we found that this phenomenon is not only in healthy people, but also in patients with high blood pressure. These findings are reasonable, and this may be because with the increase of age and the continuous rise of blood pressure, hypoxia caused by reduced blood flow and abnormal neurotransmitter transmission caused by continuous resistance led to obvious atrophy of the nerve nuclei in the basal ganglia.…”
Section: Discussionmentioning
confidence: 53%
“…25, 26 In addition, previous studies have found that both the volume of BG are found to decrease with age in healthy volunteers. 27, 28 In this study, we found that this phenomenon is not only in healthy people, but also in patients with high blood pressure. These findings are reasonable, and this may be because with the increase of age and the continuous rise of blood pressure, hypoxia caused by reduced blood flow and abnormal neurotransmitter transmission caused by continuous resistance led to obvious atrophy of the nerve nuclei in the basal ganglia.…”
Section: Discussionmentioning
confidence: 53%
“…VBM facilitates the identification of brain areas associated with specific disorders, advancing our understanding of the structural changes caused by those diseases. Recently, the VBM approach has been successfully used in many ocular diseases, such as age-related macular degeneration ( Ge et al, 2021 ), blindness ( Pan et al, 2007 ), and primary angle-closure glaucoma ( Jiang et al, 2018 ). The technique has been successfully demonstrated to be reliable and credible in clarifying pathophysiological pathways and identifying aberrant anatomy in ophthalmological illnesses.…”
Section: Introductionmentioning
confidence: 99%